The Impacts of the PBT TOEFL-based Progressive and Summative Learning Measurement in a Higher Educational Institution - Caromawati, S.S., M.A, Corry (Universitas Muhammadiyah Jember, 2017)
AbstractIt is commonly found that testing policy affects learning and teaching process occurring in educational institutions. This case study investigated the impacts of employing the PBT TOEFL test as the progressive and summative tests in a higher educational institution in one of the biggest towns in Indonesia. The data was collected through observation, field notes and personal interviews with six English language lecturers to get in-depth information based on their experience. The data from the interview was later transcribed. The whole data was analyzed qualitatively. The results showed that on the macro level, the test indeed affected the policy makersâ€™ decisions that demanded the lecturers to teach to the test and expected the students to study language outside the classroom. Their decisions inevitably also affected the individuals in the micro level. It is shown that even though the testing policy contributed positive impacts, it dominantly affected language and teaching process negatively. The perceived positive impacts included the practicality of administering the test and language explicit knowledge input to the students. The perceived negative impacts were categorized into two groups: (1) the negative attitude of the lecturers toward language teaching and the studentsâ€™ negative attitude toward learning; (2) the distorted focus of language teaching and learning. These results advocate for an evaluation towards the policy for a better language learning and teaching.Keywords: second language test, testing impacts, washback, testing policyÂ